In silico study, Synthesis, Characterization and Preliminary Evaluation of Antimicrobial activity of new sulfonamide – 1,2,4-triazole derivatives - Ali. Abdulhadi. Mosleh; Zainab. A. Dakhel (Iraqi Journal of Pharmaceutical Sciences, 2025)
A new series of sulfonamide derivatives (6a-c), containing 1,2,4-triazole-3-thiol (5a-c) ring system, were synthesized and their structures were identified by using ATR-FT-IR and 1HNMR spectroscopic analytical techniques. The synthesized compounds undergo in vitro evaluation to assess their antimicrobial activity against specific strains of Gram-positive, Gram-negative bacteria, and fungi species and compare them with standard antimicrobial drugs such as sulfamethoxazole, sulfadiazine, and fluconazole. The results indicate successful synthesis of the target compounds, which exhibit high activity against, Gram-positive bacteria (S. aureus, S. pneumonia, and B. subtilis), moderate to high activity against Gram-negative bacteria (P. aeruginosa, E. coli, N. gonorrhoeae and H. pylori), and highly active against fungi species (Candida albicans). H. pylori is the most common etiology of gastric ulcers, and gastric cancer in humans. The carbonic anhydrase enzyme regulates the acid-base balance and enables survival in the highly acidic environment of the stomach. This study utilized computational techniques to screen potential carbonic anhydrase inhibitors that target H. pylori as a therapeutic approach. The synthesized compounds interact with the zinc-binding domain of the H. pylori carbonic anhydrase (4YGF) enzyme, causing disturbance of the acid-base equilibrium and affecting the ability to adapt to the acidic environment of the stomach. This, in turn, affects the pathogenicity and virulence of the H. pylori.